High performance of yolk-shell structured MnO@nitrogen doped carbon microspheres as lithium ion battery anode materials and their in operando X-ray diffraction study. (20th August 2018) - Qin, Yanmin; Jiang, Zhongqing; Rong, Haibo; Guo, Liping; Jiang, Zhong-Jie
Abstract: The MnO@nitrogen doped carbon microspheres with a yolk-shell structure (YS-MnO@NC) is reported. As an anode for lithium ion battery, the YS-MnO@NC exhibits a very high reversible capacity (1280 mA h g −1 at 0.1 A g −1 ), superior rate capability (capacities of 1090, 860, 700, 545, and 390 mA h g −1 at 0.2, 0.5, 1.0, 2.0, and 5.0 A g −1, respectively), and stable cycling performance (880 mA h g −1 at 1.0 A g −1 after 1000 cycles). The reversible capacity and cyclability of YS-MnO@NC is higher than MnO based materials reported previously. Its remarkable performance is attributable to the unique yolk-shell structure and the presence of the NC shell. Specifically, the yolk-shell structure improves its structural stability during the repeated cycles due to the presence of the internal void between the core and shell, while the NC shell increases its electric conductivity and wettability toward the electrolyte solution. Additionally, the nitrogen doped structure also promotes a strong electronic coupling between MnO and NC. The in operando X-ray diffraction studies show that the MnO core and hollow NC microsphere play comparatively equal contributions on the high performance of the YS-MnO@NC. Both the NC shell and MnO microsphere exhibit high reversibility in lithiation and delithiation. Graphical abstract: Image 1 Highlights: The yolk-shell structured MnO@NC is prepared. The MnO@NC exhibits high performance as anode for LIB. In operando XRD studies show that both MnO and NC play big contributions on Li storage. Both NC and MnO exhibit high reversibility in lithiation and delithiation.